Enfermagem humanística : contribuição para o desenvolvimento da enfermeira na unidade neonatal - Rolim, Karla Maria Carneiro (2006)
Daily tasks, carried out by nurses who work at the newborn internment unit (Unidade de Internação Neonatal), (UIN), impose an explanation of perspective in observation, practice and management, regarding their professional activities. As nurses, working in neonatology, we believe in the necessity of reflection in order to transpose obstacles, leading to a job with an emancipatory perspective. Our interest in this text is to defend the thesis that after acquiring knowledge about the Humanistic Theory of Nursing by Paterson and Zderad, and searching for the genuine dialogue with the high-risk newborn (NB), in daily activities, based on scientific and human knowledge, the nurse will be able to comprehend the meaning of well-being and better-being. Seeking to investigate the practice of the nurses´ assistances to the high-risk newborn at the UIN based on the humanistic theory, analyze the practice of the nurses´ assistance to the high-risk newborn and to elaborate a process of humanistic care to the newborn, with the nurses´ collective participation. It is about a qualitative research supported by the humanistic theory, by Paterson and Zderad developed at UIN of a maternity school in the city of Fortaleza-CE. Totaling a period, referring to data collection from March to August 2005.the subjects were tem nurses in activity at UIN. During a period of sixty (60) days, weekly meetings, which were filmed, took place for the data collection. Later, after the meetings, we used participant observation at the UIN to register the interdisciplinary communication among nurse/baby/family/equip. During the analysis, synthesis and description we tried to comprehend it under the humanistic theory by Paterson and Zderad. The data was organized and presented using frames. After the reflection of the theoretical expositions, themes extracted from speeches and the filming of the participants, and developed by the group were: demotivation, caring, interpersonal relationship environment. Regarding the demotivation theme, mental and physical fatigue sub themes, the re-work at UIN, lack of a perspective of changes and self-knowledge emerged. Regarding the caring theme, the sub themes were self-care and caring for the baby. in the environment theme, the environment of the UIN and the feelings of the nurse in the UIN environment were the emerged sub themes. In the interpersonal relationship theme, the sub theme was found to be the relationship with the interdisciplinary equip in the UIN. The process of humanistic caring for the newborn was elaborated collectively by the nurse’s, after the comprehension of the meaning of better-being at the UIN, and included all stages of the humanistic theory. We tried to comprehend the relations among speech and existence, the environment, the ambiance around the person of each nurse. We believe that the defended thesis reaches the comprehension of the nurses´ experience significance, their better-being while caring for the newborn (NB) at UIN, by the development of self-conscience, by understanding the others, by a more relating look to diversities, by the establishment of a wider vision of the reality lived through in their daily lives, by the transition of their egocentrism to sharing of their emotions, by their knowledge and their vocation; caring.